Kualitas Rumput Unggul Tropika Hasil Ensilase dengan Bakteri Asam Laktat dari Ekstrak Rumput Terfermentasi - B Santoso; B Tj Hariadi; H Manik; H Abubakar (Faculty of Animal Science, Bogor Agricultural University, 2009)
The aim of this study was to evaluate the quality of napier grass (Pennisetum purpureum) and king grass (Pennisetum purpureophoides) ensiled with addition of lactic acid bacteria (LAB) prepared from fermented grass extract (LBFG). Four treatments were napier grass without additive (EG), napier grass with 3% (v/w) of LBFG (EGL), king grass without additive (KG) and king grass with 3% (v/w) of BLEF (KGL). Ensiling was conducted in silos of 225 g capacity at room temperatures (approximately 28 °C) for 30 days. Chemical composition of silage, fermentation products and nutrient digestibility were measured. LBFG added silages were higher (P < 0.01) in LAB population but lower in pH value (P < 0.05) compared to silages without LBFG. Dry matter (DM), organic matter (OM), crude protein (CP) and NDF contents of LBFG added silages tended to have higher value than silages without LBFG. Total and individual VFA concentrations in KGL silage were lower (P < 0.05) than KG silage. In vitro DM and OM digestibility and Fleigh point in both silages with LBFG tended to be higher than silages without LBFG. It was concluded that addition of 3% (v/w) of LBFG improved the fermentation quality of napier and king grass silages, as shown by the lower pH value and NH3-N concentration, and the higher LAB population number. Key words: tropical grasses, lactic acid bacteria, silage, fermented grass extract